Physicochemical Characterization of Red Sorghum and White Sorghum Starch - Dwi Akhiriani Ramadani; Dedin Finatsiyatul Rosida (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Sorghum (Sorghum bicolor L. Moench) is a local cereal with high starch content and considerable potential as a raw material for food applications. However, the physicochemical properties of sorghum starch vary among varieties, thereby influencing its functional characteristics and suitability for food processing. This study aimed to characterize and compare the physicochemical properties of native starch extracted from red and white sorghum. The physicochemical properties evaluated included moisture content, starch content, swelling power, and water solubility. The experimental data were analyzed using analysis of variance (ANOVA) at a 95% confidence level (? = 0.05) to determine the effect of sorghum variety on the physicochemical properties of native sorghum starch. White sorghum starch exhibited higher starch content (85.73%), swelling power (2.36 g/g), and water solubility (12.49%) than red sorghum starch. Conversely, red sorghum starch showed higher moisture content (7.83%). These differences were attributed to variations in starch composition and molecular structure between the two sorghum varieties. Overall, sorghum variety significantly affected the physicochemical properties of native starch, indicating that red and white sorghum starches possess distinct functional characteristics and are suitable for different food applications.